Cultural Tourism Development Policy Through Community Based Tourism (CBT) in the Framework of Community Poverty Alleviation - Riyanto; Dinda Oktaviani; Supriono (Journal of Social Interactions and Humanities, 2023)
Setu Babakan Betawi Cultural Village is one of the interesting places as a tourist destination for Betawi cultural heritage in DKI Jakarta. This village has won an award as the 50 Best Tourism Villages. This research uses a descriptive method and a qualitative approach with a focus on the Implementation of Community Based Tourism (CBT) there. The aims of this study were: To identify and explain the implementation of CBT in the development of cultural tourism in the Setu Babakan Betawi Cultural Village; Knowing the supporting and inhibiting factors in the development of cultural tourism; and explained that tourism activities can be used as poverty alleviation in the village. The results of this study indicate that the development of cultural tourism there goes according to CBT principles, namely involving community members in decision making, ensuring that local communities receive benefits from tourism activities, ensuring environmental sustainability, and maintaining unique local character and culture. The supporting factors are cultural conditions. still maintained, local community involvement and government support, tours are free of charge. The inhibiting factors come from operational, structural and cultural. Tourism activities can alleviate poverty due to the opening of employment opportunities and increased income of local people.